Biological Diversity of Citrus Tristeza Virus (Ctv) Isolates in Spain - Ballester-Olmos, José F.; Pina, José A.; Carbonell, Emilio A.; Moreno, Pedro; Hermoso-De-Mendoza, Alfonso; Cambra, Mariano; Navarro, Luis (2017)
A survey of citrus tristeza virus (CTV) isolates was carried out in most citrus-growing areas in Spain. Twenty-two isolates were selected by geographical origin, cultivar of source tree, and symptoms observed on the host or in preliminary tests, and were biologically characterized. A wide range of variation in transmissibility by aphids and symptom intensity on nine different indicator species or scion rootstock combinations was observed among CTV isolates. Mexican lime, Citrus macrophylla, and to a lesser extent citron were the most useful hosts for characterizing these isolates, and leaf symptoms and stem pitting were the most discriminating traits. Positive correlation was observed between symptoms induced on Mexican lime and C. macrophylla, but not between the symptoms induced on these indicators under greenhouse conditions and the homologous symptoms on plants grown in the screenhouse. Some of the traits studied enabled us to establish relatively well-defined groups of isolates, but in most cases a continuous range of variation was obtained and no clear group could be defined.